4-Nitrobenzaldehyde thiosemicarbazone: a new compound derived from S-(-)-limonene that induces mitochondrial alterations in epimastigotes and trypomastigotes of Trypanosoma cruzi. Issue 7 (June 2015) - BRITTA, ELIZANDRA APARECIDA; SCARIOT, DÉBORA BOTURA; FALZIROLLI, HUGO; DA SILVA, CLEUZA CONCEIÇÃO; UEDA-NAKAMURA, TÂNIA; DIAS FILHO, BENEDITO PRADO; BORSALI, REDOUANE; NAKAMURA, CELSO VATARU
SUMMARY Trypanosoma cruzi is the causative agent of Chagas' disease, a parasitic disease that remains a serious health concern with unsatisfactory treatment. Drugs that are currently used to treat Chagas' disease are partially effective in the acute phase but ineffective in the chronic phase of the disease. The aim of the present study was to evaluate the antitrypanosomal activity and morphological, ultrastructural and biochemical alterations induced by a new molecule, 4-nitrobenzaldehyde thiosemicarbazone (BZTS), derived from S-(-)-limonene against epimastigote, trypomastigote and intracellular amastigote forms of T. cruzi. BZTS inhibited the growth of epimastigotes (IC50 = 9·2 μm), intracellular amastigotes (IC50 = 3·23 μm) and inhibited the viability of trypomastigotes (EC50 = 1·43 μm). BZTS had a CC50 of 37·45 μm in LLCMK2 cells. BZTS induced rounding and distortion of the cell body and severely damaged parasite mitochondria, reflected by extensive swelling and disorganization in the inner mitochondrial membrane and the presence of concentric membrane structures inside the organelle. Cytoplasmic vacuolization, endoplasmic reticulum that surrounded organelles, the loss of mitochondrial membrane potential, and increased mitochondrial O2ˉ production were also observed. Our results suggest that BZTS alters the ultrastructure and physiology of mitochondria, which could be closely related to parasite death.